2017
DOI: 10.1186/s13104-017-2473-4
|View full text |Cite
|
Sign up to set email alerts
|

Situational analysis of communication of HIV and AIDS information to persons with visual impairment: a case of Kang’onga Production Centre in Ndola, Zambia

Abstract: BackgroundDespite the increases in health promotion and educational programs on HIV and AIDS, lack of information and communication on HIV and AIDS for the visually impaired persons continues. The underlying factors that create the information and communication gaps have not been fully explored in Zambia. It is therefore important that, this situational analysis on HIV and AIDS information dissemination to persons with visual impairments at Kang’onga Production Centre in Ndola was conducted. The study commence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…The real and perceived level of dependence can have both positive and negative impact on both people with disabilities and their caregivers, and may further influence their decision making and prioritization for seeking healthcare services. For instance, a number of the studies indicated that people with disabilities feel less valued by their family members and that they are left to fend for themselves in finding the resources to access services, including health [41,44,[48][49][50][51]. This concern is described in the following quote by a person with visual impairment in Cameroon:…”
Section: Cultural Beliefs and Attitudinal Barriersmentioning
confidence: 99%
See 3 more Smart Citations
“…The real and perceived level of dependence can have both positive and negative impact on both people with disabilities and their caregivers, and may further influence their decision making and prioritization for seeking healthcare services. For instance, a number of the studies indicated that people with disabilities feel less valued by their family members and that they are left to fend for themselves in finding the resources to access services, including health [41,44,[48][49][50][51]. This concern is described in the following quote by a person with visual impairment in Cameroon:…”
Section: Cultural Beliefs and Attitudinal Barriersmentioning
confidence: 99%
“…It shouldn't be seen as a stand-alone. [42] In fact, as illustrated by a number of the studies, people with different types of impairments described how they were excluded from health education campaigns or opportunities due to the initiatives only targeting the mainstream, or inclusion of disability being an afterthought [42,43,46,47,49,58]. Common examples included people with visual impairments not being able to see posters, billboards, or read informational pamphlets with health education messages, or people with hearing impairments not being able to hear messages broadcasted via radio or television programs [42,45,48,56].…”
Section: Informational Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the increase in actions aimed at promoting health for blind people about sexual practices, especially the prevention of sexually transmitted infections (STIs) and acquired immunodeficiency syndrome (AIDS), this segment of the population still has limited dominance on the subject due to the failure of the communication channels, since the health services do not have materials accessible to this public (2) .…”
Section: Introductionmentioning
confidence: 99%